2001
DOI: 10.1002/app.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coupling agents on the mechanical properties of fly ash/polyester particulate composites

Abstract: Fly ash (FA)/general purpose unsaturated polyester resin (GPR) particulate composites were made. The effect of the surface treatment of FA with two different silane coupling agents (CAs) on the mechanical properties, such as the tensile, flexural, compressive, and impact strengths and hardness, of FA-GPR composites were studied. The properties of FA-CA-GPR were also compared with that of GPR and CaCO 3 -GPR. An enhancement in the tensile, flexural, compressive, and impact strengths and a decrease in the tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…It can be seen by comparing with the un-treated composites (using silica content of 10 pph) in Figure 3 that incorporating the KBM-403 could improve the flexural modulus by 75%, the modulus increasing with KBM-403 content, this view being also found by Sen and Nugay 10 and Guhanathan and Davi 16 and Guhanathan et al. 17 Both curing systems exhibited similar effect on the flexural modulus for both silica fillers. This finding was line with the work by Chaowasakoo and Sombatsompop 13 which investigated the mechanical properties of fly ash/epoxy composites using conventional and microwave curing methods.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…It can be seen by comparing with the un-treated composites (using silica content of 10 pph) in Figure 3 that incorporating the KBM-403 could improve the flexural modulus by 75%, the modulus increasing with KBM-403 content, this view being also found by Sen and Nugay 10 and Guhanathan and Davi 16 and Guhanathan et al. 17 Both curing systems exhibited similar effect on the flexural modulus for both silica fillers. This finding was line with the work by Chaowasakoo and Sombatsompop 13 which investigated the mechanical properties of fly ash/epoxy composites using conventional and microwave curing methods.…”
Section: Resultssupporting
confidence: 75%
“…They found that the tensile and dynamic mechanical properties of cured ash/UPE composites decreased with increasing ash loading, but improved by the use of 3-methacryloxy propyl trimethoxy silane coupling agent. This view was supported by the works of Guhanathan and Davi 16 and Guhanathan et al 17 for fly ash filled unsaturated polyester composites, and of Chaowasakoo and Sombatsompop 13 for fly ash filled epoxy composites. Thongsang and Sombatsompop 14 suggested that treating the fly ash by bis-(3-triethoxysilylpropyl) tetrasulfane (Si69) at 2.0-4.0 wt% could improve the mechanical properties of natural rubber vulcanizates.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Another advantage of filler treating is higher thermal stability of the composite, in comparison to the unmodified polymer. It is worth noting that better mechanical parameters were obtained for aminofunctional silanes in reported research where aminosilane was compared with vinylsilane [20][21][22].…”
Section: Introductionmentioning
confidence: 93%
“…Load bearing properties of composites depend on the effectiveness of load transferred from the matrix on to reinforcement [27,41]. Figure 11 shows the variation in tensile strength (TS), elongation at break (EB), Modulus at 100 % and 300 % elongation of the composites EOC/FA, EOC/30 h MCA-FA and EOC/ 60 h MCA-FA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%